2015
DOI: 10.3892/ol.2015.3937
|View full text |Cite
|
Sign up to set email alerts
|

DNA hypermethylation of the vimentin gene inversely correlates with vimentin expression in intestinal- and diffuse-type gastric cancer

Abstract: Abstract. T he vimentin gene is a hallma rk of epithelial-to-mesenchymal transition and has been observed to be overexpressed in various types of tumor cell line and tissue. Previous studies have reported correlations between vimentin DNA methylation levels and subsequent vimentin expression levels in solid tumors, including breast and colorectal cancer; however, to the best of our knowledge, such a correlation has not been reported for gastric cancer (GC) using Lauren classification. Therefore, the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Epigenetic regulation of vimentin expression has also been shown to play an important role in EMT and cancer progression. It has been demonstrated that vimentin promoter methylation inversely correlates with vimentin expression and disease progression in gastric cancer [25].…”
Section: Vimentin In Emtmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetic regulation of vimentin expression has also been shown to play an important role in EMT and cancer progression. It has been demonstrated that vimentin promoter methylation inversely correlates with vimentin expression and disease progression in gastric cancer [25].…”
Section: Vimentin In Emtmentioning
confidence: 99%
“…Moreover, vimentin expression is also transactivated by β-catenin/TCF binding to the Vim promoter, thus promoting tumor cell migration/invasion [24].Epigenetic regulation of vimentin expression has also been shown to play an important role in EMT and cancer progression. It has been demonstrated that vimentin promoter methylation inversely correlates with vimentin expression and disease progression in gastric cancer [25].Apart from transcriptional regulation of vimentin expression by EMT-related transcriptional drivers, vimentin expression can be regulated also by non-coding microRNAs (miRs). It has been proposed that the HIF-1a-HDAC1 complex transcriptionally inhibits miR-548an expression during hypoxia, resulting in the upregulation of vimentin that facilitates pancreatic tumorigenesis [26].…”
mentioning
confidence: 99%
“…In particular, the methylation level of the vimentin promoter inversely correlates with the expression of vimentin in gastric Open access cancer. 54 Finally, vimentin expression is also regulated by post-transcriptional mechanisms including that of noncoding microRNAs. 12 Vimentin actively participates in inflammation and immune response Targeting vimentin could have additional effects against the progression of COVID-19 by directly modulating the inflammatory response of patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the methylation level of the vimentin promoter inversely correlates with the expression of vimentin in gastric cancer. 54 Finally, vimentin expression is also regulated by post-transcriptional mechanisms including that of non-coding microRNAs. 12 …”
Section: Introductionmentioning
confidence: 99%
“…It is found in this study that the expressions of vimentin at both the gene and protein levels were significantly upregulated with the downregulation of TPM3 expression ( p <0.05), and the monoclonal stable transfected PANC-1 cell line showed the interstitial cell morphology. It has been demonstrated that35 in breast cancer,36 liver cancer,37 gastric cancer, and38 prostate cancer, the upregulated expression of vimentin enhances the proliferation, invasion, and migration of cancer cells;39 in colon cancer, the downregulation of vimentin gene expression might lower the adhesive and invasive properties of the cancer cells.During the study process, it was found that the expressions of EMT-related transcription factors (such as Snail) were upregulated after the TPM3 gene downregulation ( p <0.05), but the Twist expression was downregulated in an insignificant way ( p >0.05). Numerous studies have shown that the transcription factor Snail can bind to the E-box of the E-cadherin promoter (the core sequence is CAGGTG), downregulating the expression of E-cadherin and inducing EMT.…”
Section: Discussionmentioning
confidence: 99%